Especificação, execução e controle de alvenaria estrutural em blocos cerâmicos de acordo com a NBR 15812 - Soares, Márcia Maria Melo (Universidade Federal de São Carlos, 2011)
This dissertation refers to the specification, execution and build s control in masonry structural of ceramic blocks, according to the current standard ABNT NBR 15812 (ABNT, 2010). The specification was evaluated by testing the compressive strength of mortar, blocks, grout, prisms and walls, which are materials constituted of various combinations, in order to define their efficiency factors. The relationship between the compressive strength in hollow blocks and prism and in blocks filled up with mortar or grout has been established, showing, as result, loss of strength in prism when the mortar was dosed with excess water. Also, there was a variation in resistance of the filled prism when the executive procedure was improved by the implementation of re-densification. Finally, It was explained the execution and build s control in masonry structural of ceramic blocks, according to the existing literature and recommendations of NBR 15812 (ABNT, 2010).
Keywords: Construção civil; Alvenaria estrutural; Blocos de cerâmica; Graute; Structural masonry; Ceramic blocks; Grout; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL